Development of Films, Based on Oxidized Ipomea Batatas Starch, with Protein Encapsulation - Alvarez-Barreto, José; Viteri Narvaez, Daniela; Proaño Aviles, Juan Sebastian; Caicedo Páliz, Andrés Bernando; Grunauer Andrade, Michelle Amanda; Eguiguren, Luis Ricardo; Vargas, Michel (Revista Mexicana de Ingenieria Biomedica, 2021)
Oxidized or dialdehyde starches (DAS) have been used as biomaterials due to their biocompatibility and biodegradability; nonetheless, sweet potato (Ipomea batatas L.) starch has not been researched in this field. Films based on sweet potato DAS, mixed with native starch (NS), poly-vinyl alcohol (PVA) and glycerin have been developed to encapsulate a model protein (Bovine serum albumin, BSA), using central composite design (CCD) and surface methodology (RSM). Input variables were oxidation degree, NS concentration and polymeric mixture volume, while output variables were film´s thickness, equilibrium swelling and BSA release. DAS was obtained through hydrogen peroxide (H2O2) oxidation, and the oxidation degree is referred to as H2O2 concentration. Scanning electron microscopy revealed a rough surface, and formulations containing 10% H2O2 DAS presented micropores. Water uptake was greater with DAS than native starch, due to its hydroxyl groups shown in Fourier transformed infrared spectra. Fil thickness depended on the volume of the polymeric suspension and influenced the swelling capacity; thicker films absorbed less water. According to RSM, the optimal formulation was DAS with 5% H2O2 and 35% NS. Oxidized sweet potato starch has potential for biomaterial applications, as films developed with it can encapsulate a protein and release it in a controlled fashion.